Chagga women´s connections with nature: fostering relationality through arts-based methods - Jasmine Pearson; Joyce Joseph Massawe; Antonia Patrick Mbaruku; Ester Ibrahim Mramba; Tuyeni H. Mwampamba; Berta Martín-López (Ecosystems and People)
Relational approaches in research are now recognised as a potential pathway to fostering transformations in sustainability research. Drawing on insights from Chagga women at Mount Kilimanjaro, Tanzania, we demonstrate how relationality can inform research methods used in sustainability science by uncovering more holistic understanding of how people relate with, connect to, and value nature. Guided by a feminist ethos of care, participatory arts-based activities were held with Chagga women during focus group discussions to elicit a deeper understanding of their connections to nature. The findings reveal in-depth, contextual and embodied expressions of how Chagga women connect to nature through agricultural practices, culinary traditions, emotional experiences and shared instrumental and relational values of aesthetics, culture, reciprocity and stewardship. We advocate for relational and arts-based approaches in sustainability science that practice critical reflexivity, foster creative freedom and unravel human emotions. Such approaches can be harnessed to strengthen human-nature connectedness and promote nature’s diverse values in pursuit of sustainability transformations.